Do robots really destroy jobs? Evidence from Europe - David Klenert; Enrique Fernández-Macías; José Ignacio Antón Pérez (European Commission, Joint Research Centre (JRC), 2020)
While citizen opinion polls reveal that Europeans are concerned about the labour market consequences of technological progress, the understanding of the actual significance of this relationship is still imperfect. This paper assesses the impact of robot adoption on employment in Europe. Combining industry-level data on employment by skill-type with data on robot adoption and using different sets of fixed-effects techniques, we find that robot use is linked to an increase in aggregate employment. Contrary to some previous studies, we do not find evidence of robots reducing the share of low-skill workers across Europe. Since the overwhelming majority of industrial robots is used in manufacturing, our findings should not be interpreted outside of the manufacturing context. However, the results still hold when including non-manufacturing sectors and they are robust across a wide range of assumptions and econometric specifications.
Keywords: 330; Robots; jobs; employment; low-skilled workers; inequality; European Union; economicactivities